The creative engineer what can you do to spark new ideas?. - Selinger, C. (IEEE spectrum)
This article is all about improving the creativity of engineers. It discusses some steps on how to become more creative to develop fresh ideas for improving the products being designed and built. One of the reasons why engineers are not considered creative is because they often don't start with a blank sheet of paper each time they do something. Every engineer's core mission is to try to improve the utility of things, to design products or processes that will solve the problems better, faster, and cheaper. Most engineers are familiar with the class creativity-enhancing technique of brainstorming that too often fails to produce anything satisfying or practical. But there is one better way called synetics, that combines brainstorming with a more disciplined harvesting of ideas. The discussion includes not just those involved on the project but also a representative who ask the group to address a specific problem. Another way of being more creative is to look things from different perspectives, and encourage others to welcome new ideas, or at least not stifle them.